MFO INDUCTION IN ATLANTIC SALMON (SALMO SALAR)DURING AND AFTER EXPOSURE TO BASS STRAIT CRUDE OIL - Gagnon, Marthe Monique; Holdway, D. (1998)
Biochemical markers of exposure (mixed function oxygenase: MFO as determined by ethoxyresorufin O-deethylase (EROD) activity) and of effect(sorbitol dehydrogenase:SDH) were investigated for use during and after exposure of Atlantic salmon (salmo salar) to low levels of Bass Strait crude oil water-accommodated fraction (WAF) and dispersed crude oil. EROD activity was significantly induced after only two days of exposure to dispersed oil,while four days of exposure were necessary to significantly induce EROD in the WAF-exposed salmon. Following the termination of exposure,EROD induction remained elevated for eight days in both the WAF-exposed and the dispersed oil-exposed fish. Dispersing the oil using Corexit 9527 produced similar EROD activity levels in salmon relative to WAF only. Serum SDH activity confirmed that no hepatocellular injury was caused by exposure of salmon to these levels of WAF or to dispersed Bass Strait crude oil. It is concluded that MFO induction,as measured by changes in EROD activity,can be used for confirmation of low-level exposure of commercial salmon stocks to petroleum contaminated waters for up to eight days after the event.